The Role of Health Education in Primary Health Care Facilities in Supporting Exclusive Breastfeeding Success: A Scoping Review - Kusteja, Nadya Fauzia; Anwar, Ruswana; Pramatirta, Akhmad Yogi; Susiarno, Hadi; Gurnida, Dida Akhmad; Irianti, Setyorini (JTP - Jurnal Teknologi Pendidikan, 2025)
Health education in primary healthcare facilities serves as a key factor in facilitating the success of exclusive breastfeeding. Primary healthcare facilities, such as community health centers and clinics, serve as initial points for mothers to understand that exclusive breastfeeding, along with using the right breastfeeding techniques, greatly benefits their baby’s health and growth. Through effective health education programs, healthcare providers can enhance mothers' knowledge and skills in breastfeeding, which in turn can reduce failures in exclusive breastfeeding practices. Research shows that mothers who receive health education on breastfeeding techniques those educated on the topic tend to achieve exclusive breastfeeding success more often than those without such knowledge. A scoping A review approach adhering to the PRISMA-ScR criteria was utilized, with literature searches conducted through scientific literature platforms, for example PubMed, Google Scholar, and Scopus. The results of effective health education in primary healthcare facilities can help achieve national targets for exclusive breastfeeding and improve the health of mothers and children.